Pemberian Motivasi Kerja Dalam Meningkatkan Kinerja Pegawai Negeri Sipil Pada Dinas Pendidikan Kabupaten Muna Barat - Aldzi Fahmi, Wa Ode; Gunawan, Gunawan; Elwan, La Ode Muhammad (Universitas Halu Oleo, 2021)
The purpose of this research is to determine the work motivation of employees at the West Muna district education office and to determine the performance of civil servants at the West Muna district education office. The research methodology used in this study is a descriptive method that seeks to describe the intended phenomenon. The data obtained from interviews with informants amounted to 3 people who were directly involved in the process of providing work motivation in improving the performance of civil servants. Then the data obtained is then analyzed and interpreted and a conclusion is drawn. The results of research on direct motivation at the Education Office of West Muna Regency are quite good, this can be seen from the provision of direct motivation in the form of salary bonuses, praise to employees at the West Muna Regency Education Office who have good performance. Then the performance of employees at the Education Office of West Muna Regency is quite good. The quality of work employees work with discipline, make the best use of working time and understand their respective duties and responsibilities in doing the work given.